GLOBAL DETERMINANTS OF ENTRY MODE CHOICE - Tulung, Joy Elly (Journal of Indonesian Economy and Business, 2010)
Since several decades, a lot of academic attention has been given to entry mode decisions of firms, and which factors, in which contexts, are important determinants to take into consideration. Especially interesting for researchers is what influences the choice for a certain entry mode. A general limitation of this research stream seems to be that theempirical testing is limited to firms of a particular part of the world. This paper has developed six propositions. These propositions all concern a certain variable whichinfluences the entry mode choice. The variables have been justified in the transaction cost theory, the resource based. Following the theories, the relationship between assetspecificity, R&D intensity, firm size and international experience is said to be positive with the entry mode choice, and cultural distance and country risk are negatively related. Most propositions have been confirmed. view and institutional theory. These variables are asset specificity, R&D intensity, firm size, cultural distance, country risk and internationalexperience.Keywords: Entry mode theory, transaction cost theory, resource based view, institutional theory